Enhancing speakins skills: Dogme ELT outcomes in the engineering EFL context - Ali, Imanat; Zuraina, Ali; Ezihaslinda, Ngah (Penerbit UMP, 2025)
English has been used since long as a tool of communication among the people around the globe. It remains relevant because the diversity and versatility of the population is still increasing (Burns & Richards, 2018). English is taught at school level to help students become globalised. It is the most spoken language in the world; 53 countries’ official language and is used by 400 million people for communication globally (Ilyosovna, 2020). Speaking skills of the students must be up to the standard to achieve the speaking goal in the countries where English is taught as a foreign or second language. Students can contribute to the future if they are taught and prepared with effective teaching methods and approaches.